Combination of Deep Breathing Relaxation and Murottal Reducing Post Chemotherapy Nausea Intensity in Nasopharyngeal Cancer (NPC) Patients - Agus Suryono; Fredi Setia Nugraha; Fakhruddin Akbar; Yunie Armiyati (Media Keperawatan Indonesia, 2020)
Nasopharyngeal Cancer (NPC) is the 3rd most common type of cancer in Indonesia after cervical and breast cancer. The method for controlling the growth of cancer cells is chemotherapy which has side effects of nausea. Post-chemotherapy nausea makes the patient uncomfortable and if not treated properly will cause complications. Management of nausea can be done with a combination of deep breathing relaxation and murottal.  The objective of the study to analyze the effect of a combination of deep breathing relaxation and murottal on the intensity of nausea in NPC patients after chemotherapy. The research method was a quasi-experiment one group pre-post-test design on 30 samples of post-chemotherapy NPC patients.  The results of the study showed that nausea intensity before and after given a combination of deep breathing and murottal obtained p-value 0,000 (p-value <0.05). There is a significant difference between nausea intensity before and after the combination of deep breathing and murottal relaxation. The combination of deep breathing and murottal breathing can reduce the intensity of nausea in NPC patients after chemotherapy.